Growth rates, seed size, and physiology: do small-seeded species really grow faster? - Turnbull, L; Paul-Victor, C; Paul-Victor, C; Schmid, B; Schmid, B; Purves, D; Purves, D (2008)
Relative growth rate (RGR) is currently the most commonly used method for measuring and comparing species' intrinsic growth potential. Comparative studies have, for example, revealed that small-seeded species have higher RGR, leading to the common belief that small-seeded species possess physiological adaptations for rapid growth that would allow them to outgrow large-seeded species, given sufficient time. We show that, because RGR declines as individual plants grow, it is heavily biased by initial size and does not measure the size-corrected growth potential that determines the outcome of competition in the long-term. We develop a daily growth model that includes a simple mechanistic representation of aboveground and belowground growth and its dependency on plant size and environmental factors. Intrinsic growth potential is encapsulated by the size-independent growth coefficient, G. We parameterized the model using repeated-harvest data from 1724 plants of nine species growing in contrasting nutrient and temperature regimes. Using information-theoretic criteria, we found evidence for interspecific differences in only three of nine model parameters: G, aboveground allocation, and frost damage. With other parameters shared between species, the model accurately reproduced above- and belowground biomass trajectories for all nine species in each set of environmental conditions. In contrast to conventional wisdom, the relationship between G and seed size was positive, despite a strong negative correlation between seed size and average RGR, meaning that large-seeded rather than small-seeded species have higher size-corrected growth potential. Further, we found a significant positive correlation between G and frost damage that, according to simulations, causes rank reversals in final biomass under daily temperature changes of +/- 5 degrees C. We recommend the wider use of this new kind of plant growth analysis as a better way of understanding underlying differences in species' physiology; but we recognize that RGR is still a useful metric if considering the potential rate of population increase in empty habitats.